Catalytic Allylic Chlorination of Natural Terpenic Olefins Using Supported and Nonsupported Lewis Acid Catalysts - Ayoub Abdelkader Mekkaoui; Mouhsine Laayati; Hamza Orfi; Larbi El Firdoussi; Soufiane El Houssame (Journal of Chemistry)
A mild and convenient method for the allylic chlorination of naturally occurring terpenic olefins was investigated in the presence of different supported and non-supported Lewis acid catalysts. The reaction has been tested on carvone as a model substrate in the presence of sodium hypochlorite as chlorine donor. The scope and limitations of transition metal-based Lewis acid catalysts, stoichiometry, and substrate structure were evaluated. Among the iron precursors used, FeCl3 and FeCl2 provide the promise of a general approach to allylic or vinylic chlorination reaction. Various terpenic olefins were examined in the presence of FeCl3/NaOCl combination system. The catalytic chlorination proceeds under mild conditions with short reaction time and shows a high selectivity affording the corresponding chlorides in good to excellent yields.